Different parvalbumin and GABA expression in human epileptogenic focal cortical dysplasia. (13th May 2016) - Medici, Valentina; Rossini, Laura; Deleo, Francesco; Tringali, Giovanni; Tassi, Laura; Cardinale, Francesco; Bramerio, Manuela; de Curtis, Marco; Garbelli, Rita; Spreafico, Roberto
Summary: Objective: Several studies have reported that inhibitory networks are altered in dysplastic tissue obtained from epilepsy surgery specimens. A consistent decrease in the number of inhibitory interneuronal subpopulation that expresses parvalbumin (PV) was reported in postsurgical tissue from patients with focal cortical dysplasia (FCD). We tested if the decrease in PV protein expression observed in epileptic tissue corresponds to a parallel impairment in the γ‐aminobutyric acid (GABA)ergic compartment. Methods: We analyzed postsurgical tissue from 30 surgically treated patients who underwent surgery for intractable epilepsy including 26 patients with FCD (types I, II, and III) and 4 patients without any microscopic visible lesion (cryptogenic) as controls. Serial sections were processed using in situ hybridization with GAD‐65 and GAD‐67 probes and immunocytochemistry with antibody against PV. The density of inhibitory PV‐immunoreactive interneurons in relation to GABAergic cells was estimated in controls and in all different pathologic groups by using a two‐ and three‐dimensional (2D and 3D) cell‐counting technique. Field fraction and line profile analyses were added to estimate immunostaining proportion and distribution of PV signal generated in gray matter. Results: A reduction of PV‐positive cells and PV‐immunoreactivity was observed exclusively in FCD type I/III specimens compared with cryptogenic tissue from control patients with a poor postsurgical outcome. In FCD type II, a profound rearrangement in the cortical distribution of PV immunoreactivity was observed, without a quantitative reduction of the number of neurons and terminals. In situ hybridization did not reveal significant variations of GAD expression in any FCD subtype. Significance: Our study suggests a preservation of inhibitory networks in FCD postsurgical tissue, demonstrated by a substantial normal count of GABAergic neurons. A selective PV expression impairment is demonstrated in FCD type I and III and an abnormal, but not reduced, distribution of PV cells and terminals is confirmed in type II FCD. Possible functional consequences are discussed.